Insight into GATA1 transcriptional activity through interrogation of cis elements disrupted in human erythroid disorders - Wakabayashi, Aoi (Proc Natl Acad Sci U S A, 2016)
Whole-exome sequencing has been incredibly successful in identifying causal genetic variants and has revealed a number of novel genes associated with blood and other diseases. One limitation of this approach is that it overlooks mutations in noncoding regulatory elements. Furthermore, the mechanisms by which mutations in transcriptional cis-regulatory elements result in disease remain poorly understood. Here we used CRISPR/Cas9 genome editing to interrogate three such elements harboring mutations in human erythroid disorders, which in all cases are predicted to disrupt a canonical binding motif for the hematopoietic transcription factor GATA1. Deletions of as few as two to four nucleotides resulted in a substantial decrease (>80%) in target gene expression. Isolated deletions of the canonical GATA1 binding motif completely abrogated binding of the cofactor TAL1, which binds to a separate motif. Having verified the functionality of these three GATA1 motifs, we demonstrate strong evolutionary conservation of GATA1 motifs in regulatory elements proximal to other genes implicated in erythroid disorders, and show that targeted disruption of such elements results in altered gene expression. By modeling transcription factor binding patterns, we show that multiple transcription factors are associated with erythroid gene expression, and have created predictive maps modeling putative disruptions of their binding sites at key regulatory elements. Our study provides insight into GATA1 transcriptional activity and may prove a useful resource for investigating the pathogenicity of noncoding variants in human erythroid disorders.